Beyond repetition: the role of gray zone alleles in the upregulation of FMR1-binding miR-323a-3p and the modification of BMP/SMAD-pathway gene expression in human granulosa cells - Vilkaite, Adriana; Nguyen, Xuan Phuoc; Güzel, Cansu Türkan; Gottschlich, Lucas; Bender, Ulrike; Dietrich, Jens Erik; Hinderhofer, Katrin; Strowitzki, Thomas; Rehnitz, Julia (International journal of molecular sciences, 2025)
The Fragile X mental retardation type 1 gene (FMR1) contains a CGG triplet cluster of varied length (30 repeats on average) located in its 5′ UTR. In its premutated state (54-200 repeats), FMR1 contributes to the pathogenesis of premature ovarian insufficiency (POI). Its gray zone alleles (41-54 repeats) are supposed to impair the ovarian function as well. In the case of a CGG repeat length > 200, Fragile X syndrome occurs. Post-transcriptional expression of FMR1 is regulated by microRNAs. Although miR-323a-3p overexpression suppresses FMR1 in various tissues, this relationship has not been evaluated in the human ovary. Additionally, this microRNA targets SMADs, which are suggested regulators of ovarian cell proliferation, growth, and function. This study investigated how FMR1 allele lengths with CGG repeat numbers n < 55 (normal and gray zone genotypes) relate to miR-323a-3p expression and how they may impact associated SMAD expression in human granulosa cells. COV434 cells and patient-derived GCs were used to evaluate FMR1, miR-323a-3p, and BMP/SMAD-pathway member expression levels. Briefly, miR-323a-3p was significantly upregulated in GCs of the gray zone group compared to the normal allele group (p < 0.0001), while the FMR1 level did not vary. Furthermore, the gray zone group showed a significant upregulation of BMPR2, SMAD1, SMAD4, and SMAD9. In contrast, the miR-323a-3p transfection of COV434 cells significantly downregulated SMAD3, SMAD4, SMAD5, and SMAD9, while the FMR1 and SMAD1 levels remained stable. Our findings highlight a CGG repeat number-dependent upregulation of miR-323a-3p and an alteration of the BMP/SMAD pathway, suggesting that these changes happen and contribute to impaired ovarian function independently.
Gesehen am 26.09.2025